A unidade didática dos livros didáticos de português do ensino fundamental II: um olhar ao longo dos tempos - Cargnelutti, Joceli (2015)
In recent years the interest and the number of studies on the emergence of each school subject and its changes over time have increased. Motivated by these studies, we direct our attention to the Portuguese language in an attempt to increase knowledge of its constitution through textbooks, looking specifically at the constitution of teaching units of Portuguese language teaching collections of Elementary School II, published before PNLD (in the 1960 s, 1970 s and 1980 s) and during the application of PNLD (editions of 1999, 2002, 2005, 2008 and 2011). We aimed to identifying the structure of teaching units presented in each collection, score the prioritized teaching objects, know how verbal-visual language appears as a constitutive element of the units structures and identify the continuities, displacements and changes in teaching units over the period investigated. The research was supported in Bakhtin s theoretical perspective, which allowed us to understand teaching units from a socio-historical process, and the textbook as one of the tools responsible for ensuring the acquisition of knowledge in that process. The research made it possible to understand that the teaching unit consists of a predominantly fixed sequence of often invariable activities, prioritizing in it a teaching purpose; also, it is always permeated by a verbal-visual configuration progressively extended. Furthermore, the analysis made possible to realize small and progressive changes in teaching units, i.e., they are small in relation to close sentences, but they become more significant since they are best understood (BAKHTIN, [1974] 2000) as time becomes distant in a dialogue with other texts.